VALUASI KUPON OBLIGASI PT. BPD LAMPUNG TBK. MENGGUNAKAN OPSI MAJEMUK CALL ON CALL TIPE EROPA - Revaldo Mario; Diah Safitri; Agus Rusgiyono (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
A bond is a debt capital market instrument issued by a borrower, who is then required to repay to the lender/investor the amount borrowed plus interest at maturity, and also known as fixed-income securities, and therefore the bond is an attractive investment in the financial sector. Most theories about the financial statistics is based on the bond without coupon bonds. Whereas, in fact most companies issue bonds with a coupon. Option is an agreement or contract which provides the right and not an obligation for the holder of a contract to buy (call option) or sell (put option) a particular asset at a price and time have been set. Underlying assets can be stocks, bonds, warrants and more. One type of option trading is a European type option is an option that can be used only at the time of maturity. The approach used in the valuation of bond coupons is to use the theory of Europe style compound option call on call. European style compound option call on call is the type of European call options with underlying assets are call options. Final project aims to get the value of equity and the value of liabilities on the bonds PT BPD Lampung Tbk with a coupon rate when the bond before maturity (compound option strike price) and a coupon rate of the bond at maturity (the strike price of the call option). The current bond coupon payments prior to maturity was conducted on July 9, 2017 and a coupon payment at maturity conducted on 9 October 2017. Based on the results of data processing with the help of open source software R 3.1.1, the value of the equity is greater than the value of liabilities.Keywords: bond, call option, compound option, coupon bond, equity, liability